A Letter to the Scientific Community (London Journal of Research In Science: Natural and Formal, 2024)
Today's scientific information presents a moment for investigating the true cosmos. The contradictions within modern physics necessitate an examination of the fundamental issue of space, a question that has been deferred for over 2500 years. During the era of Aristotle, understanding of the cosmos was insufficient, leading Western philosophical thought to pivot entirely toward the philosophy of cosmic material, abandoning the philosophy of cosmic origin and the existence of divinity within space, relegating these inquiries to theology. The debate between Newton and Leibniz over absolute space left physics with inadequate information, subject to skepticism and lacking conclusion. Today, modern physics, systems science, physical cosmology, and other scientific disciplines provide information on time, mechanics, the composition of cosmic spaceboth material and immaterial. Based on the philosophical thoughts of Daoism, Buddhism, and dialectical materialism, there may now exist an opportunity to investigate the existence of divinity within space and to study the cosmic origin. It is hoped that scientists will reconsider and investigate the issue of immaterial existence within space, and reevaluate absolute space (Liu,0-Dimensional Universe - Absolute space test,liu (2021)?liu?2020?). This may be the key to resolving the contradictions between quantum mechanics and relativity, and I request your Consider publishing the letter.
Keywords: Disconnections strategies; Organic synthesis; Retrosynthesis; Synthetic plan; Target molecule.1; molecular docking; Bioactive compounds; H. pylori; Binding affinities; and MD simulations; rhenium alloys; molybdenum; thin coatings; electrochemical deposition; binary alloys; current density.; Space Absolute Space Relative Space Basic Energy intelligence Energy Matter Energy Information